Police photography - Miller, Larry 1953-; Marin, Norman (Elsevier, 2015)
Quality photographs of evidence can communicate details about crime scenes that otherwise may go unnoticed, making skilled forensic photographers invaluable assets to modern police departments. For those seeking a current and concise guide to the skills necessary in forensic photography, Police Photography , Seventh Edition, provides both introductory and more advanced information about the techniques of police documentation. Completely updated to include information about the latest equipment and techniques recommended for high-quality digital forensic photography, this new edition thoroughly describes the techniques necessary for documenting a range of crime scenes and types of evidence, including homicides, arson, and vehicle incidents. With additional coverage of topics beyond crime scenes, such as surveillance and identification photography, Police Photography , Seventh Edition is an important resource for students and professionals alike.